CARDIOVASCULAR REMODELING IN MILD HYPERTENTION: ROLE OF SOLUBLE RECEPTOR FOR ADVANCED GLYCATION END PRODUCTS. (June 2018) - Grossi, A.; Corso, R.; Tandurella, N.; Moretti, S.; Cavallaro, G.; Test, L. Robustelli; Agostinis, M.; Pierobon, V.; Tavecchia, L.; Mancuso, V.; Mongiardi, C.; Montalbetti, L.; et al.
Abstract : Objective: To assess the correlation between soluble receptor for advanced glycation end products (sRAGE) and office, 24 hours and central blood pressure (BP) and heart morpho-functional parameters in untreated mild hypertensive patients. Design and method: We enrolled 74 patients, 35–55 years-old, with mild untreated hypertension, free from cardiovascular diseases or diabetes, not smokers. 52 normotensives age, sex and anthropometric parameters-matched were enrolled in the control group. Each subject underwent office and 24 hours BP measurement, arterial tonometry (central BP, Pulse Wave Velocity-PWV), echocardiography (left ventricular mass-LVM, atrial size), carotid ultrasonography (intima media thickness-IMT) and blood tests, with sRAGE dosage too. Results: sRAGE dosage was similar in hypertensives and normotensives (891 ± 697.9pg/ml vs. 900 ± 560.4pg/ml). There was no difference also between patients with normal glucose and with impaired fasting glucose, as well as between subjects with and without metabolic syndrome. In hypertensives, we found a negative correlation between sRAGE and LVM (r:−0.24, p:0.04), also confirmed by multivariate analysis (β:−0.223, p:0.04). A negative correlation was also observed between sRAGE and left atrial (LA) antero-posterior diameter (r:−0.37, p:0.002), LA volume (r:−0.34, p:0.004, confirmed by multivariate analysis β:−0.214, p:0.03) and BSA-indexed LA volume (r:−0.30, p:0.01). sRAGE correlated also with right atrial (RA) area (r:−0.38, p:0.001), but not with RA volume (r:−0.24, p:0.08). There was no correlation between sRAGE and office, 24 hours and central BP, PVW, carotid-IMT, glycemia, HOMA-index and uricaemia. Conclusions: Correlations between sRAGE and LVM, LA and RA dimensions suggest how advanced glycation end products could play a role in cardiovascular remodeling. Mild hypertension and young age of our population may explain lack of differences between sRAGE dosage in hypertensives and normotensives. Importantly, all the observed correlations were found in absence of drugs interference.